Determination of 10-Hydroxy-2-Decenoic Acid Content – a Marker in Several Commercial Royal Jelly Products Collected in Vietnam - Anh, Duong Hong; Tuan, Vu Minh; Huyen, Van Thi Thanh; Huy, Nguyen Manh; Dam, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
The optimized capillary electrophoresis (CE) was applied to separate and detect the 10-hydroxy-2-decenoic acid (10-HAD) in royal jelly products. The method only requires that the sample solution need to be centrifuged and filtered before analyzed by the home-made capillary electrophoresis system. Firstly, 10-HDA was separated in a fused silica column with a diameter of 50 um using 20 mM Tris/Acetic buffer (pH 8.5) as a background electrolyte and a separation voltage of -17kV. Then, 10-HDA was detected by capacitively coupled contactless conductivity detection (C 4 D) with the migration time less than 8 minutes. Nine commercial products of royal jelly with Vietnamese and imported origin including pure royal jelly cream, lyophilized royal jelly (powder and gel) and honey with royal jelly were collected for analysis. The results of this study showed that content of 10-HDA were detected in the range of 0.5 mg/g to 23.1 mg/g. Using paired t test showed that the difference between results obtained from CE-C 4 D method and from HPLC method as a reference method was not statistically significant. Keywords: 10-HDA, royal jelly products, CE-C 4 D. References   [1] M. Viuda Martos, Y. Ruiz Navajas, J. Fernández López, J.A. Pérez Álvarez, Functional properties of honey, propolis, and royal jelly”, Journal of food science 73 (2007) 117-124. https://doi:10.1111/j. 1750-3841.2008.00966.x. [2] M.F. Ramadan, A. Al-Ghamdi, Bioactive compounds and health-promoting properties of royal jelly: A review, Journal of Functional Foods 4 (2012) 39- 52. https://doi.org/10.1016/j.jff. 2011. 12.007. [3] Dimitrios Kanelis, Chrysoula Tananaki, Vasilis Liolios, Maria Dimou, Georgios Goras, Maria Anna Rodopoulou, Emmanuel Karazafris, and Andreas Thrasyvoulou, A suggestion for royal jelly specifcations, Archives of Industrial Hygiene and Toxicology 66 (2015) 275-284. Https://doi: 10.1515/aiht-2015-66-2651. [4] Brazil Ministério Da Agricultura e Do Abaste Imento. Secretaria De Defesa Agropecuária. Instrução normativa nº3, de 19 de janeiro de 2001. Regulamento técnico para fxação de identidade e qualidade de geléia real, Regulamento técnico para fxação de identidade e qualidade de geléia real liofilizada. Http:// www.engetecno.com.br/port/ legislacao/mel_geleia_real.htm. [5] Mahmut Genc¸ Abdurrahman Aslan, Determination of trans-10-hydroxy-2-decenoic acid content in pure royal jelly and royal jelly products by column liquid chromatography, Journal of Chromatography A. 839 (1999) 265 – 268. Http://doi: 10.1016/s0021-9673(99)00151-x. [6] F. Ferioli, E. Armaforte, M.F. Caboni, Comparison of the Lipid Content, Fatty Acid Profile and Sterol Composition in Local Italian and Commercial Royal Jelly Samples” Journal of the American Oil Chemists' Society, 91(2014) 875-884. Http://doi. org/10.1007/s11746-014-2446-x. [7] J. Kim, J. Lee, Quantitative analysis of trans-10-hydroxy-2-decenoic acid in royal jelly products purchased in USA by high performance liquid chromatography”, Journal of Apicultural Science, 54 (2010) 77-85. Https://pdfs.semanticscholar. org/e85f/dfc1823d778a40c ca2eefa4be8ba4b4d98 6c.pdf. [8] C.I. Pavel, L.A. Mărghitaş, D.S. Dezmirean, L.I. Tomoş, V. Bonta, A. Şapcaliu, A. Buttstedt, Comparison between local and commercial royal jelly-use of antioxidant activity and 10-hydroxy-2-decenoic acid as quality parameter”, Journal of Apicultural Research 53 (2014) 116-123. https:// doi.org/10.3896/IBRA.1.53.1.12. [9] Mahmut Genc¸ Abdurrahman Aslan, Determination of trans-10-hydroxy-2-decenoic acid content in pure royal jelly and royal jelly products by column liquid chromatography, Journal of Chromatography A, 839 (1999) 265 – 268. Https://doi:10.1016/s0021-9673(99)00151-x. [10] Jinhui Zhou, Xiaofeng Xue, Yi Li, Jinzhen Zhang and Jing Zhao, Optimized determination method for trans-10-hydroxy-2-decenoic acid content in royal jelly by high-performance liquid chromatography with an internal standard, Journal of AOAC International, 90(2007) 244-249. https://www.ncbi.nlm.nih.gov/pubmed/17373456. [11] Federico Ferioli, Gian Luigi Marcazzan, Maria Fiorenza Caboni, Determination of (E)-10-hydroxy-2-decenoic acid content in pure royal jelly: A comparison between a new CZE method and HPLC”, J. Sep. Sci .30 (2007) 1061-1069. Http://doi:10.1002/jssc.200600416. [12] Orlando Muñoz, Susana Decap, Francisco Ruiz, José Arbildua, Octavio Monasterio, Determination of 10- hydroxy-2-decenoic acid in royal jelly by capillary electrophoresis, J. Chil. Chem. Soc., 56 (2010) 738-740. http://dx.doi.org/10.4067/S0717 97072011000300004.